2018
DOI: 10.2147/dmso.s141700
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive therapy for glucose control in patients with type 1 diabetes

Abstract: Type 1 diabetes mellitus (T1DM) is characterized by relative or absolute insulin deficiency. Despite treatment with insulin therapy, glycemic goals are not always met, and insulin therapy is sometimes limited by adverse effects, including hypoglycemia and weight gain. Several adjunctive therapies have been evaluated in combination with insulin in patients with T1DM to improve glycemic control while minimizing adverse effects. Pramlintide, an amylin analog, can improve glycemic control, primarily through loweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
(149 reference statements)
0
15
0
1
Order By: Relevance
“…Clinical recommendations for individuals with HbA1c levels above target may differ based on weight status, especially given the complicated physiologic relationships between weight and glycemia 31. For example, approaches for under or normal weight individuals with elevated HbA1c may be centered on insulin intensification, while approaches for overweight individuals could balance the glycemic benefits of insulin intensification with the potential for weight gain via concurrent behavioral, pharmacological, or surgical interventions 32. Although the American Diabetes Association Standards of Care currently state that the risks and benefits of agents adjunctive to insulin therapy in T1D require further evaluation, early studies have shown improvements in glycemic control as well as body weight associated with metformin, GLP1-receptor agonists, and SGLT-2 inhibitors 32 33.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical recommendations for individuals with HbA1c levels above target may differ based on weight status, especially given the complicated physiologic relationships between weight and glycemia 31. For example, approaches for under or normal weight individuals with elevated HbA1c may be centered on insulin intensification, while approaches for overweight individuals could balance the glycemic benefits of insulin intensification with the potential for weight gain via concurrent behavioral, pharmacological, or surgical interventions 32. Although the American Diabetes Association Standards of Care currently state that the risks and benefits of agents adjunctive to insulin therapy in T1D require further evaluation, early studies have shown improvements in glycemic control as well as body weight associated with metformin, GLP1-receptor agonists, and SGLT-2 inhibitors 32 33.…”
Section: Discussionmentioning
confidence: 99%
“…For example, approaches for under or normal weight individuals with elevated HbA1c may be centered on insulin intensification, while approaches for overweight individuals could balance the glycemic benefits of insulin intensification with the potential for weight gain via concurrent behavioral, pharmacological, or surgical interventions 32. Although the American Diabetes Association Standards of Care currently state that the risks and benefits of agents adjunctive to insulin therapy in T1D require further evaluation, early studies have shown improvements in glycemic control as well as body weight associated with metformin, GLP1-receptor agonists, and SGLT-2 inhibitors 32 33. Subgroups with adequate glycemic control and overweight or obesity may be specifically targeted for more intensive behavioral modifications such as dietary interventions to address obesity with special attention towards avoiding hypoglycemia associated with decreased caloric or carbohydrate intake 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ряд пилотных работ с применением инкретиновой модели терапии при СД 1 типа был весьма оптимистичен [49,50]. В патогенезе поздних осложнений СД 1 типа, в частности диабетической нефропатии, с успехом изучались и протекторные негликемические эффекты ГПП-1, включая даже тех пациентов, которые получали заместительную почечную терапию программным гемодиализом или перенесли трансплантацию почки [51].…”
Section: терапевтический потенциал инкретиновых гормонов при сдunclassified
“…Although insulin technology and its administration have shown remarkable advances, individuals with T1DM have continued difficulties in maintaining target glucose levels and sometimes suffer AE, such as severe hypoglycemia and weight gain [ 61 ]. Therefore, the evaluation of adjunctive therapies in individuals with T1DM is required.…”
Section: Adjunctive Therapies To Insulin Therapy In T1dmmentioning
confidence: 99%